The Current State of Aquaculture in Laguna de Bay - Danilo C. Israel (Philippine Institute for Development Studies (PIDS), 2007)
This paper presents some of the preliminary results and findings of an ongoing study jointly conducted by the Southeast Asian Fisheries Development Center (SEAFDEC AQD) and Philippine Institute for Development Studies (PIDS), which assesses the current state of aquaculture in Laguna de Bay. The study uses primary and secondary data. The primary data were gathered through interviews with key informants and a cross-section survey of fishpen and fishcage operators and their operations in Laguna de Bay conducted in 2007. The secondary data were gathered from the published statistical indices of institutional sources and other relevant literature. The results of the study indicate that aquaculture in Laguna de Bay is a vibrant industry that includes not only fishpen and fishcage operators but also various participants in its input and product markets. Furthermore, they show that aquaculture contributes significantly to fish production in the lake as well as to national aquaculture and fisheries production. The results of the study also indicate that while aquaculture in Laguna de Bay has been an important economic contributor locally and nationally, it has been facing numerous problems over time that constrain its development. Of these, environment-related problems, lack of access to cheap capital, obstruction of navigational lanes by fishpens, existence of illegal fishpens, poaching, and overall limited support from the government were considered very serious by aquaculture operators. These problems, therefore, may be the ones needing the most attention.
Keywords: 330; aquaculture; Laguna de Bay; aquaculture problems; fishpens; fishcages; environment-related problems